Pengaruh Return On Sale, Earning Per Share, Economic Value Added, dan Market Value Added Terhadap Nilai Perusahaan Pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia - Yancik Syafitri; Lia Indah Sari (Universitas Tridinanti, 2019)
ABSTRACKThe purpose of this study was to determine how much influence Return on Sale, Earning per Share, Economic Value Added, and Market Value Added as independent variables together (simultaneous) and individually (partial) to the Corporate Value as the dependent variable in LQ-45 company listed on the Indonesia Stock Exchange. The population of this study is all LQ-45 companies listed on the Stock Exchange in 2015-2017. The sample selection uses a purposive sampling method. The data used is secondary data in the form of financial statements. The results of this study state that simultaneously Return on Sale, Earning per Share, Economic Value Added, and Market Value Added have a significant effect on Company Value. Partially, Return on Sale and Market Value Added have a significant effect on Company Value but Earning per Share and Economic Value Added do not significantly influence the Company ValueKeywords : Return on Sale, Earning per Share, Economic Value Added, Market Value Added, Company Value